Behavior of a shock-accelerated heavy cylindrical bubble under nonequilibrium conditions of diatomic and polyatomic gases - Singh, Satyvir (2022)
The physical problem based on a shock-accelerated bubble has long been a fascinating subject in the study of the Richtmyer-Meshkov (RM) instability. In this study the behavior of a shock-accelerated heavy cylindrical bubble under the nonequilibrium conditions of diatomic and polyatomic gases is investigated numerically. For this purpose, a two-dimensional system of unsteady physical conservation laws derived from the Boltzmann-Curtiss kinetic equations is solved by employing an explicit mixed-type modal discontinuous Galerkin method with uniform meshes. For validation, the numerical results are compared with available experimental and computational results, and are found to be in good agreement. The results demonstrate that the effects of different physical properties, including thermal nonequilibrium and bulk viscosity associated with the viscous excess normal stress on diatomic and polyatomic gases, play a significant role in describing the RM instability during the interaction between a planar shock wave and a heavy bubble. The effects of diatomic and polyatomic gases result in a substantial change in the flow morphology with complex wave patterns, vortex creation, vorticity generation, and bubble deformation. In contrast to monatomic gas, the generation of larger rolled-up vortex chains, a different kind of outward jet formation, and a large mixing zone with strong and large expansion are observed in diatomic and polyatomic gases. A detailed study of the effects of diatomic and polyatomic gases is investigated through the vorticity generation, degree of nonequilibrium, the evolution of enstrophy, and dissipation rate. Furthermore, the time variations of the shock trajectories and the interface scales are investigated from the viewpoint of quantitative analysis. Finally, the effects of nonequilibrium parameters, including bulk viscosity and index of inverse power law, are also investigated. The present work can be seen as a supplement to the RM instability research to examine the nonequilibrium effects of diatomic and polyatomic gases on the dynamics of a shock-accelerated heavy cylindrical bubble.